Why Do Central Banks Go Weak? - Oulidi, Nada (IMF Working Papers; Working Paper ;, 2009)
Determinants of central banks' profitability are studied using a statistical analysis of their balance sheets, country characteristics, and the macroeconomic and institutional environments in which they operate. Central banks at both tails of the distribution of profits generally operate in poorer countries with more troubled macroeconomic and institutional environments. For these central banks, profitability is strongly influenced by fiscal dominance and, to a lesser extent, by how actively central banks used their balance sheet for monetary policy purposes.